2022
DOI: 10.1038/s12276-022-00799-9
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1224-5p modulates osteogenesis by coordinating osteoblast/osteoclast differentiation via the Rap1 signaling target ADCY2

Abstract: MicroRNAs (miRNAs) broadly regulate normal biological functions of bone and the progression of fracture healing and osteoporosis. Recently, it has been reported that miR-1224-5p in fracture plasma is a potential therapy for osteogenesis. To investigate the roles of miR-1224-5p and the Rap1 signaling pathway in fracture healing and osteoporosis development and progression, we used BMMs, BMSCs, and skull osteoblast precursor cells for in vitro osteogenesis and osteoclastogenesis studies. Osteoblastogenesis and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…ADCY2 is a versatile regulator capable of playing diverse roles in disease. It has been reported that ADCY2 gene polymorphisms are involved in the genetic susceptibility to osteoporosis and fracture nonunion 21 . Estradiol promotes the expression of cAMP via miR‐148a/152‐ADCY2 to regulate the growth and function of mesenchymal stem cells 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADCY2 is a versatile regulator capable of playing diverse roles in disease. It has been reported that ADCY2 gene polymorphisms are involved in the genetic susceptibility to osteoporosis and fracture nonunion 21 . Estradiol promotes the expression of cAMP via miR‐148a/152‐ADCY2 to regulate the growth and function of mesenchymal stem cells 22 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ADCY2 gene polymorphisms are involved in the genetic susceptibility to osteoporosis and fracture nonunion. 21 Estradiol promotes the expression of cAMP via miR-148a/152-ADCY2 to regulate the growth and function of mesenchymal stem cells. 22 Moreover, ADCY2 is associated with severe chronic obstructive pulmonary disease and lung function levels, 23 and ADCY2 interaction with air pollution is vital for asthma development.…”
Section: Mir-616-3p Acts As a Tumor Suppressor In Aml Cellsmentioning
confidence: 99%
“…The G protein-coupled receptor pathway is nowadays a hot spot in cancer immune research, and some members of GPCRs are actually demonstrated as having a role as prognostic factors in a variety of cancers [50][51][52].In KEGG enrichment analysis, the main enrichments were in the neuroligand-receptor interaction, phospholipase D signaling pathway, oxytocin signaling pathway, CGMP-PKG signaling pathway, and Rap1 signaling pathway. Among them, the RAP1 signaling pathway, which is regulated by other interacting genes in osteoporosis and colorectal cancer, mediates the value-added of tumor cells or osteoblasts [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…254 miR-1224-5p is a vital bone osteogenic regulator and alleviates osteoporosis by targeting ADCY2 to promote osteoblast differentiation through the Rap1 signalling pathway and inhibiting RANKL-induced osteoclast differentiation. 255 miR-26a-5p is enriched in urine-derived stem cell extracellular vesicles (USCs-EVs). 256 By inhibiting HDAC4, miR-26a-5p derived from USCs-EVs can activate the HIF-1α and vascular endothelial growth factor A (VEGFA) pathway to facilitate the differentiation of osteogenic precursor cells, thus alleviating diabetic osteoporosis (DOP).…”
Section: The Role Of Mirnas In Metabolic Diseasementioning
confidence: 99%